Rhodolith Physiology Across the Atlantic: Towards a Better Mechanistic Understanding of Intra- and Interspecific Differences - Schubert, Nadine; Peña, Viviana; Salazar, Vinícius W.; Horta, Paulo A.; Neves, Pedro; Ribeiro, Cláudia; Otero-Ferrer, Francisco; Tuya, Fernando; Espino, Fernando; Schoenrock, Kathryn; Hofmann, Laurie C.; Le Gall, Line; et al. (Frontiers in Marine Science, 2022)
Coralline algae are important components in a large variety of ecosystems. Among them, rhodoliths are a group of free-living coralline red algae that cover extensive coastal areas, from tropical to polar regions. In contrast to other ecosystem engineers, limited research efforts preclude our understanding of their physiology, underlying mechanisms, drivers and potential differences related to species under varying environments. In this study, we investigated the photosynthetic and calcification mechanisms of six Atlantic rhodolith species from different latitudes, as well as intra-specific differences in one species from four locations. Laboratory incubations under varying light levels provided simultaneous photosynthesis- and calcification-irradiance curves, allowing the assessment of inter- and intra-specific differences on the coupling between these two processes. Stable isotope analysis and specific inhibitor experiments were performed to characterize and compare carbon-concentrating mechanisms (CCMs), as well as the involvement of specific ion-transporters for calcification. Our findings showed significant differences in rhodolith physiological mechanisms that were partially driven by local environmental conditions (light, temperature). High variability was found in the coupling between photosynthesis and calcification, in CCM-strategies, and in the importance of specific ion transporters and enzymes involved in calcification. While calcification was strongly correlated with photosynthesis in all species, the strength of this link was species-specific. Calcification was also found to be reliant on photosynthesis- and light-independent processes. The latter showed a high plasticity in their expression among species, also influenced by the local environment. Overall, our findings demonstrate that (1) rhodolith calcification is a biologically-controlled process and (2) the mechanisms associated with photosynthesis and calcification display a large variability among species, suggesting potential differences not only in their individual, but also community responses to environmental changes, such as climate change.